Obstetrics and Fecal Incontinence - Chin, Kathleen (Clinics in Colon and Rectal Surgery, 2014)
Anal incontinence (AI) can be a debilitating condition for women following vaginal delivery. Operative vaginal delivery and anal sphincter laceration are important risk factors for the development of postpartum AI. Obtaining a comprehensive delivery history, along with a thorough physical examination of the perineum, vagina and rectum may aid the clinician in the diagnosis of an anal sphincter defect. Sonographic imaging can also assist in identifying sphincter defects. The treatment of AI may include a combination of dietary modification, medications that promote constipation, pelvic floor physical therapy, biofeedback, anal sphincteroplasty, and/or sacral neuromodulation.
Keywords: postpartum anal incontinence; anal sphincter defect; obstetric injury